Psychological portrait of an aging person—experiencing loss in late adulthood - Stefańska, Alena (Health Promotion & Physical Activity, 2025)
Contemporary literature shows a growing interest in the topics of aging, old age or late adulthood. According to the WHO, late adulthood begins at the age of 60. We are not all equal in the face of passing time. Adapting to aging involves, among other things, the ability to cope with feelings of loss, which are a dominant part of the portrait of an aging person. The literature on the subject mentions experiences such as the loss of health, physical fitness, physical and sexual attractiveness. Changes at this stage of life also include aspects such as social and economic status, which is associated with entering retirement. The development of public awareness of health, hygiene, nutrition as well as medical advances and technological progress have led to an increase in average life expectancy. However, in order for the ‘autumn of life’ to be cheerful, it is important to be in good physical condition, have a positive mental attitude, accept aging and find elements in it, that will allow to enjoy this stage of life. The article describes the most important biological, psychological and social changes which aging people have to face. It also indicates how older people can adapt to these challenges and at the same time maintain a sense of meaning.